Gender Earnings Gap in the Formal Labor Market in Turkey - Cebeci, Tolga (World Bank, Washington, DC, 2016)
Gender disparities in Turkey remain considerable despite Turkish government’s recent public policy initiatives aimed at increasing gender equity in Turkey. Overall gender equity ranking of Turkey in the gender gap 2012 report. Gender equity is identified as a key area in the 2012-2015 country partnership strategy of the World Bank Group (WBG) in Turkey. One of the projects initiated to move WBG’s gender agenda in Turkey further is the technical assistance project on promoting gender equity in labor markets and entrepreneurship. Using novel datasets, this study aims to contribute to the project through providing a better understanding of different dimensions of the gender gap in employment and particularly earnings. Key findings of this paper are as follows: (i) the gap between men and women in participation emerges with the early exit of women, particularly those low educated, after marriage; (ii) partly due to exit of low educated women after marriage, female employees, on average, have less work experience than male employees; (iii) compared to men, women work in higher paying sectors, sub-sectors, and firms within sub-sectors. Yet, women earn less than the men working in the same firm; (iv) female employees are more concentrated in larger firms especially in the East and the North regions of the country; and (v) once all observable characteristics are taken into account, it is hard to argue that earnings discrimination against women in the formal labor market of Turkey is large. Section one gives introduction. Section two and three are dedicated to the investigation of gender gap in labor market participation. Section four and five analyze the gender gap in earnings. Section six presents conclusion and policy implications.